Toroidal Spectral Drawing - Ming-Hsuan Kang; Jing-Wen Gu (Axioms, 2022)
We give a deterministic drawing algorithm to draw a graph onto a torus, which is based on the usual spectral drawing algorithm. For most of the well-known toroidal vertex-transitive graphs, the result drawings give an embedding of the graphs onto the torus.